Menggugah Kemandirian Ekonomi Desa Melalui Kopi: Sinergi Petani dan Wanita Tani Sinjai dalam Hilirisasi Produk - Muhsin, Muh Arief; Nur Abdi, Muhammad; Maddo, Irwan; Makmur (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service program was implemented in Bonto Tengnga Village, Sinjai Regency, with the main objective of enhancing the village’s economic independence through the empowerment of two partner groups, namely the Balantieng Farmers Group and the Women Farmers Group Persatuan. Both groups faced several challenges, including limited skills in coffee cultivation management, suboptimal utilization of coffee husk waste, and a lack of innovation in developing local processed food products. To address these issues, the program was conducted through several stages, including socialization, needs identification, technical training, intensive mentoring, and follow-up evaluation. The training activities focused on improving technical skills such as proper coffee cherry picking, plant maintenance and fertilization, and the production of compost from coffee husks as a value-added agricultural by-product. For the women farmers group, the program emphasized product diversification by developing various types of crackers made from bananas, cassava, and taro with assorted flavors, as well as training in product packaging and marketing strategies. In addition to technical training, the program also strengthened institutional capacity through bookkeeping and task management workshops to improve organizational governance. The results showed a significant improvement in the partners’ knowledge, practical skills, and confidence in managing local resources productively, efficiently, and sustainably. The collaborative approach between the farmers group and the women farmers group proved effective in creating an integrated economic value chain within the village. Overall, this program serves as a model for developing rural economic independence through coffee-based downstream processing that enhances community welfare and sustainable local economic resilience.